Impact of various intensities and frequencies of non-occupational physical activity on the risk of dementia among physically independent older adults: the Japan Gerontological Evaluation Study. (July 2021) - Arafa, A.; Eshak, E.S.; Shirai, K.; Cadar, D.; Iso, H.; Tsuji, T.; Kanamori, S.; Kondo, K.
Abstract: Objectives: The aim of this study was to investigate the association between different intensities and frequencies of non-occupational physical activity (PA) and the risk of dementia among Japanese older adults. Study design: This was a prospective cohort study. Methods: A total of 2194 participants aged ≥65 years from the Japan Gerontological Evaluation Study were followed up between 2010 and 2016. The standardised dementia scale of the long-term care insurance system was used to identify incident dementia, whereas non-occupational PA (<2 or ≥2 times/week on each intensity: light, moderate and vigorous) was assessed using a questionnaire. Cox regression was used to compute the hazard ratios (HRs) and 95% confidence intervals (CIs) for incident dementia. Results: After adjustment for sociodemographic and medical characteristics, the following frequencies and intensities of non-occupational PA, compared with no non-occupational PA at all, were associated with a reduced risk of dementia: light PA ≥2 times/week (HR = 0.61, 95% CI: 0.38–0.97), moderate PA <2 times/week (HR = 0.46, 95% CI: 0.28–0.76), moderate PA ≥2 times/week (HR = 0.57, 95% CI: 0.36–0.91), vigorous PA <2 times/week (HR = 0.40, 95% CI: 0.21–0.74) and vigorous PA ≥2 times/week (HR = 0.29, 95% CI: 0.15–0.57). In the sex-specific analysis, moderate PA <2 times/week and vigorous PA ≥2 times/week were associated with a reduced risk of dementia in men, whereas light and moderate PA ≥2 times/week and all frequencies of vigorous PA were associated with a reduced risk of dementia in women. Conclusions: Practicing non-occupational PA was associated with a reduced risk of dementia among Japanese older adults.